2015
DOI: 10.1093/ckj/sfv018
|View full text |Cite
|
Sign up to set email alerts
|

Heroin crystal nephropathy

Abstract: In this paper we present an interesting case of acute kidney injury and severe metabolic alkalosis in a patient with a history of heavy heroin abuse. Urine microscopy showed numerous broomstick-like crystals. These crystals are also identified in light and electron microscopy. We hypothesize that heroin crystalizes in an alkaline pH, resulting in tubular obstruction and acute kidney injury. Management is mainly supportive as there is no known specific therapy for this condition. This paper highlights the utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…Meanwhile, a prospective cohort study reported that reduced eGFR was associated with Heroin [ 42 ]. Lastly, a relatively new mode of AKI has come to light as “heroin crystal nephropathy” by Bautista et al in 2015 [ 43 ]. This case showed that volume depletion along with elevated urinary pH leads to crystallization of Heroin or its metabolites in renal tubules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, a prospective cohort study reported that reduced eGFR was associated with Heroin [ 42 ]. Lastly, a relatively new mode of AKI has come to light as “heroin crystal nephropathy” by Bautista et al in 2015 [ 43 ]. This case showed that volume depletion along with elevated urinary pH leads to crystallization of Heroin or its metabolites in renal tubules.…”
Section: Discussionmentioning
confidence: 99%
“…This case showed that volume depletion along with elevated urinary pH leads to crystallization of Heroin or its metabolites in renal tubules. Heroin being adulterated with sodium bicarbonate is the likely explanation [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…L'hé roïne, qui peut cristalliser à pH alcalin, peut entraîner des tubulopathies cristallines [21,22].…”
Section: Rhabdomyolyse Et Tubulopathies : Cocaïne He´roïne Amphe´taunclassified
“…Par ailleurs, des glomé ruloné phrites membrano-prolifé ratives (GNMP) ont é té dé crites aprè s consommation de cannabis [49], de cocaïne [50], d'hé roïne [21] et d'amphé tamine [51].…”
Section: Autres Glome´rulopathiesunclassified
“…This is most likely due to a hypersensitivity response to adulterants in the heroin preparations, including nonsteroidal anti-inflammatory drugs. Finally, heroin crystal nephropathy has been described recently in the setting of heavy heroin use, and it is likely to occur in the setting of acute tubular injury (6). It is characterized by tubular accumulation of finely granular to fluffy basophilic crystals on light microscopy; the crystals appear as broomstick crystals on urinalysis.…”
mentioning
confidence: 99%